The Role of Religious Identity in Political Affiliation and Voter Behaviour Among Muslim Youths in Nima - Shamhuna, Abdul Aziz; Hidayah, Dwi Khonisa Nurul (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study looks into how a person’s religious self-view can steer their political leanings and voting choices among young Muslims in Nima. It kicks off by blending together stories from interviews and focus groups with numbers pulled from surveys, a mix-methods approach that, frankly, doesn’t follow a strict recipe but rather paints a broad, sometimes unexpected picture. Generally speaking, the data hint that faith isn’t just a quiet background detail; rather, it shapes opinions and guides voter behaviour. Many participants openly discussed how their strong, almost instinctive sense of civic duty, one that’s tied up with their religious beliefs – drives not only reactive voting but also a proactive push to see government reflect these values. This active engagement, by the way, isn’t confined to politics alone. There’s a compelling suggestion here that public health efforts could really benefit if policymakers take note of how closely religious and political identities are interwoven. In most cases, aligning health policies with the values of these young community members might boost trust and improve outcomes in a way that feels naturally inclusive. Altogether, the essay adds a nuanced voice to the ongoing conversation about identity politics, hinting that when we understand why religious communities vote the way they do, we can better foster both vibrant political participation and more thoughtful public health strategies.